2021
DOI: 10.1049/tje2.12092
|View full text |Cite
|
Sign up to set email alerts
|

A review of power system predictive failure model for resilience enhancement against hurricane events

Abstract: Natural events such as hurricanes usually cause unimaginable destruction to the electric power system infrastructures across the globe leading to large‐scale power outages. While the transmission network offers relatively high resilience to the hurricane extreme wind speed intensity (HEWSI), the distribution power system network (DPSN) is always the worst hit. To enhance the DPSN against hurricane events, both the pre‐ and post‐event power system resilience enhancement techniques can be reviewed, and their lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…However, the proposed model in [21] was never tested with a proactive system optimization model for impact assessment as regards the reduction in the expected load loss. Other literature such as [16], [19], [22] also supported the proposed BN-DSN predictive model as a better operational planning decisionmaking tool for the distribution system operators (DSO) compared to the combined statistical DSN's line FC-MCS-SCENRED predictive algorithm. However, studies to corroborate or support this claim are largely unexplored.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the proposed model in [21] was never tested with a proactive system optimization model for impact assessment as regards the reduction in the expected load loss. Other literature such as [16], [19], [22] also supported the proposed BN-DSN predictive model as a better operational planning decisionmaking tool for the distribution system operators (DSO) compared to the combined statistical DSN's line FC-MCS-SCENRED predictive algorithm. However, studies to corroborate or support this claim are largely unexplored.…”
Section: Introductionmentioning
confidence: 89%
“…The papers suggested the need to change the reactive operational resilience improvement techniques proposed by many researchers in assessing the resilience improvement of the DSN against hurricane events, to a more defensive proactive operational resilience improvement approach [14]. In Omogoye et al, [15], [16] the works of the literature showed that the prospective statistical regression methods such as the generalized linear model (GLM), generalized additive model (GAM), system treeapproach mining models (STMM), and power system topology (PST)-based resilience evaluation approach which include the predictive DSN line's FC-MCS have been utilized to assess the hurricane-caused DSN line faults in the past. The GLM, GAM, and STMM approaches are grouped as systemlevel damage predictive algorithms [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation